RANCANG BANGUN APLIKASI PEMANTAU DATA WIRELESS SENSOR NETWORK UNTUK PERINGATAN DINI TERHADAP BANJIR - Kautsar, Muhammad Syakir; Jusak, Jusak; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
Frequent floods occurred in several areas in Indonesia annually that eventually cause who are affected by the flood. More often floods arrive at night when most people were fast asleep. This means that peaople are mostly not ready when disaster comes. This is one of the reasons why long-range early-detection flood devicewas designed. Not only improve the accuracy of detection of the flooding but it will be able to monitor so there will be an accurate precaution signal of this disaster at the night time.Monitoring the water level of the river situation in real time using Wireless Sensor Network (WSN) technology. WSN is a wireless network infrastucture that uses sensors to monitor physical or environmental conditions that are connected to the network. To display data transmitted WSN nodes, made the application of software visual basic 6. In this application generates the system displays the status of the water level of the river (prototype), status of the device, warning when the flood and the estimated time of flooding occurs. The time estimates obtained from the calculation of the average speed of change in the water level before.